Representation of The RAON Management Crewing System in the Management of Seafarers’ Documents at PT Inkor Dunia Samudra - Fasya Aulia Sabrina; Agus Leonard Togatorop; Fitri Zuhriyah; Edy Kurniawan (Asian Journal Science and Engineering, 2025)
This research is motivated by issues in the management of seafarers’ documents at PT Inkor Dunia Samudra, which continues to face challenges such as the lack of a centralized archiving system, the high complexity of documents requiring regular validation, and limited staff capacity to monitor document completeness. The purpose of this study is to determine the extent of the influence of the Management Crewing System (RAON System) on the management of seafarers’ documents and how the system serves as a solution to administrative challenges within the company. This research employs a quantitative approach using simple linear regression analysis. Data were collected through a likert-scale-based questionnaire distributed to 48 respondents, consisting of internal staff from PT Inkor Dunia Samudra and representatives of the ship owner. Data analysis was conducted using SPSS 30, with the application of simple regression analysis and t-test. The results show that the Management Crewing System (RAON System) has a significant influence on the management of seafarers’ documents, as evidenced by the t-test result where t-value > t-table (5.981 > 1.679). This is further supported by the coefficient of determination (R Square) from the regression equation Y = 8.444 + 0.417X, which yields a value of 0.438 or 43.8%. The system has proven effective in increasing efficiency, reducing administrative errors, and accelerating document validation processes. Therefore, it is recommended that the company continue to improve the RAON System by expanding its features and providing regular training to ensure optimal use by all staff.